Hubungan Metode Qiro’ati dengan Kemampuan Membaca Al-Qur’an Peserta Didik Kelas VII di MTs Darul Muttaqien - Mubarok, Zahid; Ashriyanti, Dita Fitri; Dewi, Reni Sinta (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Qiro'ati is one of the methods of reading the Qur'an that was first discovered by KH. Dachlan Salim Zarkasiy from Semarang in 1963. And Madrasah Tsanawiyah Darul Muttaqien is one of the many institutions in Indonesia that uses the Qiro'ati method to improve and improve the reading of the Qur'an of its students. This study discusses the relationship of the Qiro'ati method to the ability to read the Qur'an of students. The research used is quantitative research. The research subjects were seventh grade students at MTs Darul Muttaqien. In collecting the data using questionnaires and tests. The results of this study indicate that there is a relationship between the Qiro'ati method and the ability to read the Qur'an of seventh grade students at MTs Darul Muttaqien. In addition to school or madrasah, the Qiro'ati learning process is also carried out in a dormitory environment by creating a Al-Qur'an group or halaqoh. The learning steps used are three stages, namely initial learning, core learning, and final learning. Keywords: Qiro'ati Method, Qur'an Reading Ability